Dimethyl ether production via methanol dehydration using Fe3O4 and CuO over γ–χ–Al2O3 nanocatalysts. (15th November 2020) - Armenta, M.A.; Maytorena, V.M.; Flores–Sánchez, L.A.; Quintana, J.M.; Valdez, R.; Olivas, A.
Graphical abstract: Highlights: DME production by methanol dehydration using Fe3 O4 and CuO. Fe3 O4 /γ–χ–Al2 O3 reached selectivity to DME of 100%. The Ea of the Fe3 O4 /γ–χ–Al2 O3 was lower than the value of CuO/γ–χ–Al2 O3 . Abstract: Selective Fe3 O4 and CuO catalysts supported on γ–χ–Al2 O3 were successfully prepared using the facile controlled precipitation method. The catalysts Fe3 O4 /γ–χ–Al2 O3 and CuO/γ–χ–Al2 O3 showed excellent catalytic activity at low temperatures between 250 and 290 °C and 1 atm pressure. According to the experimental works, Fe3 O4 /γ–χ–Al2 O3 showed better activity and selectivity at 250 °C, related to better dispersion of its active phase within the pores of γ–χ–Al2 O3 and its lower activation energy, Ea = 46.4 kJ/mol. At 250 °C, Fe3 O4 /γ–χ–Al2 O3 presented a higher theorical partial pressure of DME related to its better catalytic performance in the methanol dehydration reaction.